HUBUNGAN TINGKAT PENGETAHUAN IBU TENTANG PAUD DENGAN KEIKUTSERTAAN ANAK PADA PAUD DI DESA KARANGBANGUN JUMAPOLO KABUPATEN KARANGANYAR - Lilik Sriwiyati; Endang Dwi Ningsih; Lusiana Ambarningrum (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2015)
Background Knowledge comes from learning, it occurs when a person sensed toward an object. Knowledge or cognitive ability is a very important domain affecting someone’s behaviour (overt behavior). The participation in children in Early Childhood Education Programs is affected by their parent’s knowledge.Research purpose of this research is to seek the relation between mother’s knowlegde level of Early Childhood Education Programs with the children’s participation in Early Childhood Education Programs at Karangbangun Village, Karanganyar Regency.Methods This research is a relational study and use cross sectional method. This research has two variables, the first variable is mother’s knowledge level of Early Childhood Education Programs as a independent variable and the second variable is children’s participation as a dependent variable. The samples were 30 responden selected by using total sampling method. Collecting data use questionaire paper. Data analysis use Chi square Test with p 0,05.Results of this research are the children’s participation is 25% on whose mother’s knowlegde level considered as average and 78,57% on whose mother’s knowlegde level considered as high. Statistical test use Chi Quadrat with the result p=0,003.The conclusion of this research is that there is a relation between mother’s knowlegde level of Early Childhood Education Programs with the children’s participation in Early Childhood Education Programs at Karangbangun Village, Karanganyar Regency.Keyword: Knowlegde of Early Childhood Education Programs and children’s participation in Early Childhood Education Programs